Study of the monosaccharide composition of vegetable marrow leaves by the GC/MS method and determination of their antimicrobial activity - Iosipenko, Olena; Kyslychenko, Viktoriia (Annals of Mechnikov's Institute, 2022)
Introduction. Vegetable marrow (Cucurbita pepo L. ssp. pepo L.) of Cucurbitaceae family is a source of polysaccharides: sugars, pectins and dietary fibers. They are easily absorbed by the body, without causing irritation of the gastric and intestines. Dietary fibers of vegetable marrow fruits adsorb toxic substances and excess cholesterol well, remove them from the body. Vegetable marrow fruits activate digestion processes, improve the motor and secretory functions of the gastric and intestines, and prevent the development of atherosclerosis. They are recommended to be included in the diet for the kidneys, liver, gastric and intestines diseases, as well as for treatment of hypertension. However, there is almost no information on the phytochemical study of vegetable marrow leaves in the available scientific literature. The aim of the work was to identify and assay of carbohydrates by gas chromatography/mass spectrometry method (GC/MS) of vegetable marrow leaves, as well as conducting a study of the antimicrobial activity of an aqueous extract from the specified raw material. Material & methods. The raw materials used for research were harvested in August 2020 in Kharkiv region (Ukraine). The monosaccharides composition was determined by GC/MS method on gas chromatograph Agilent 6890N with 5973inert mass detector (Agilent Technologies, USA). Samples were analyzed on a capillary column HP-5MS of 30 m length and an internal diameter of 0.25 mm, the thickness of the stationary phase was 0.25 μm. The first set up was at oven temperature of 160°C and held for 8 min, then raised to 240°C at the rate of 5°C/min and kept at this point for 6 min. Helium was used as a carrier gas at a constant flow rate of 1.2 cm3/min. Detection was performed in the SCAN mode at the width range of 38–400 m/z. Identification of monosaccharides was based on comparing their retention times with retention times of standards of the mass spectral library NIST 02. Quantitative analysis was performed by adding a solution of the internal standard to the tested samples. Sorbitol solution was used as an internal standard. Reference test cultures were used for bacteriological research: Staphylococcus aureus ATCC 25923, Escherichia coli ATCC 25922, Pseudomonas aeruginosa ATCC 27853, Bacillus subtilis ATCC 6633, Proteus vulgaris ATCC 4636, Candida albicans ATCC 885-653. The antimicrobial activity of the preparations was determined by the diffusion method of "wells" using the Muller-Hinton medium followed by the measurement of the diameters of the zones of inhibition of the growth of microorganisms. When evaluating the antibacterial activity of the tested extract, the following criteria were used: the absence of growth or the presence of a zone of growth retardation up to 10 mm was considered as a lack of sensitivity, 10–15 mm as low, 15–25 mm as moderate, and exceeding 25 mm as high sensitivity of the microorganism to the studied extract. Experiments were carried out in three repetitions. Results & discussion. The GC/MS method was used to determine the qualitative composition and quantitative content of carbohydrates in vegetable marrow leaves. Free carbohydrates included D-arabinose, D-glucose, D-galactose and D-saccharose were identified. D-rhamnose, D-arabinose, D-xylose, D-mannose, D-glucose, D-galactose and D-fructose were also identified in plant raw material after acidic hydrolysis and derivatization with acetylated aldononitriles. Free carbohydrate D-saccharose was present in vegetable marrow leaves in the greatest amount (11.09 mg/g). In the vegetable marrow leaves predominant ones were D-glucose 1.38 mg/g, D-galactose 0.11 mg/g and D-arabinose 0.09 mg/g. Also, monosaccharides after hydrolysis in the vegetable marrow leaves were identified. In the raw material the prevailing ones were D-glucose (32.39mg/g), D-galactose (8.26 mg/g), D-arabinose (2.84 mg/g), D-xylose (2.68 mg/g), D-rhamnose (2.37 mg/g), D-mannose (1.25 mg/g) and D-fructose (0.53 mg/g). Aqueous extract from vegetable marrow leaves showed a reliably pronounced antimicrobial activity against all test strains of microorganisms. Conclusions. The monosaccharide composition of vegetable marrow leaves was studied for the first time. The obtained results show the prospects of their further in-depth study. In addition, the fairly high antimicrobial activity of the leaves of white-fruited vegetable marrow suggests the possibility of creating an antimicrobial medicinal product based on them. The obtained data can also be used for standardization and development of quality control methods for the studied raw materials. Keywords: vegetable marrow, leaves, monosaccharide, gas chromatography/mass spectrometry method, antimicrobial activity.